SOSIALISASI PROGRAM RUJUK BALIK PADA PASIEN YANG BERKUNJUNG DI WILAYAH KERJA PUSKESMAS AIR TAWAR - Yulia Yulia; Gusni Rahma; Gusrianti Gusrianti (Universitas Alifah Padang, 2026)
The Referral Program (PRB) is a service within the National Health Insurance system that allows patients with chronic diseases to receive follow-up care at primary healthcare facilities after being hospitalized. Data on JKN patient visits in 2023 shows that Air Tawar Community Health Center had the lowest number of visits in Padang City, with 13,571 visits. However, many patients still do not understand the benefits, mechanisms, and procedures for implementing PRB, resulting in suboptimal utilization. The purpose of this community service activity is to increase knowledge and foster positive attitudes among elderly patients regarding the benefits, mechanisms, and procedures of the Referral Program (PRB). The method used was health education for 50 elderly patients visiting Air Tawar Community Health Center in Padang City. The community service implementation method involved providing education through leaflets about the benefits of the referral program for patients with non-communicable diseases. Evaluation was conducted using questionnaires before and after the activity to measure changes in participants' knowledge and attitudes. The results of the activity showed an increase in participants' understanding and attitudes towards PRB. The proportion of participants with good knowledge increased to 76%, while the proportion with a positive attitude toward PRB implementation increased to 84% after participating in the outreach program. This activity demonstrates that outreach through education and two-way communication can increase knowledge and shape positive attitudes toward the Referral Program among elderly patients. It is hoped that similar educational activities can be conducted continuously to support the optimization of PRB implementation and improve the quality of care for patients with chronic diseases.